Dissociative symptomatology in cancer patients - Civilotti, Cristina; Castelli, Lorys; Binaschi, Luca; Cussino, Martina; Tesio, Valentina; Di Fini, Giulia; Veglia, Fabio; Torta, Riccardo (Frontiers in Psychology, 2015)
Introduction: The utilization of the post-traumatic stress disorder (PTSD) diagnostic spectrum is currently being debated to categorize psychological adjustment in cancer patients. The aims of this study were to: (1) evaluate the presence of cancer-related traumatic dissociative symptomatology in a sample of cancer patients; (2) examine the correlation of cancer-related dissociation and sociodemographic and medical variables, anxiety, depression, and post-traumatic stress symptomatology; (3) investigate the predictors of cancer-related dissociation. Methods: Ninety-two mixed cancer patients (mean age: 58.94, ds = 10.13) recruited from two hospitals in northern Italy were administered a questionnaire on sociodemographic and medical characteristics, the Karnofsky Scale to measure the level of patient activity and medical care requirements, the Hospital Anxiety and Depression Scale (HADS) to evaluate the presence of anxiety and depression, the Impact of Event Scale Revised (IES-R) to assess the severity of intrusion, avoidance, and hypervigilance, and the Peritraumatic Dissociative Experiences Questionnaire (PDEQ) to quantify the traumatic dissociative symptomatology. Results: 31.5% of participants report a PDEQ score above the cutoff. The results indicated that dissociative symptomatology was positively correlated with HADS scores (HADS-Anxiety: r = 0.476, p < 0.001; HADS-Depression: r = 0.364, p < 0.001) and with IES-R scores (IES-R-Intrusion: r = 0.698, p < 0.001; IES-R-Avoidance: r = 0.619, p < 0.001; IES-R- Hypervigilance: r = 0.681, p < 0.001). A stepwise regression analysis was performed in order to find the predictors of cancer-related traumatic dissociative symptomatology. The results converged on a three predictor model revealing that IES-R-Intrusion, IES-R-Avoidance, and IES-R-Hyperarousal accounted for 53.9% of the explained variance. Conclusion: These findings allow us to hypothesize a specific psychological reaction which may be ascribed to the traumatic spectrum within the context of cancer, emphasizing the close relationship between the origin of dissociative constituents which, according to the scientific literature, compose the traumatic experience. Our results have implications for understanding dissociative symptomatology in a cancer population and can help develop clinical programs of prevention and support for patients.